Nekotorye aspekty skorostno-silovoj podgotovki kvalificirovannych biatlonistok - Sergeev, G. A.; Polomoshnov, D. I. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
The present article presents the results of maximal upper-body speed strength testing in female biathletes aged 18-19 years old by using Ski Erg Concept 2. Testing was made before and right after pre-season training in order to see the dynamics of upper body power development. The aim of the study was to evaluate the dynamics of upper body power development during pre-season training. The results describe absolute and relative maximal upper body power changes among the female biathletes before and after pre-season training. The results showed a significant lack of relative upper body power in female biathletes before the beginning of the pre-season training. The averaged results of the group in absolute upper body test were rated as "above average", however, the averaged relative power was rated as "average", even by power scale for 14-15 years old athletes. By the end of pre-season training 6 of 8 athletes have significantly improved their absolute and relative upper body power, however the averaged power of the group was still rated as "average". The present results show that there is a significant lack of the absolute and relative upper body power in female biathletes who use classical training model. These findings should be taken into consideration by the coaches. It seems necessary to pay more attention to speed-strength and power training in female athletes in pre-season in order to perform on high level during competitive season.